THE DEVELOPMENT OF THE INDUSTRIAL COMPLEX OF IVANO-FRANKIVSK REGION - Taraievska , L.S.; Verbovska , L.S.; Petryna , M. Yu. (The actual problems of regional economy development, 2017)
Overcoming the effects of deep crisis and exit the trajectory of constant growth is impossible without the development of the industrial complex, which must secure a high level of innovative business enterprises to create broad opportunities for competitive production of the product as on the internal and external so. The leading role of industry in the economy of Ukraine in general and Ivano -Frankivsk region in particular, is determined, first of all, that, that, protecting all branches of the national economy work tools and new materials, it is the most active factor in scientific and technical progress and extended plays in whole. Among other industries holding industry isolated complex functions and rejonowo forming. The article analyzed the structure of the industrial complex and based on that set out the main trends in the development of Ivano -Frankivsk.